Analysis of Key Performance Indicators to Study the Growth and Development of Selected Software Companies in India - Karpagavalli, V. (Indian Journal of Computer Science, 2022)
The Indian software industry plays a significant role in developing the national economy, from an inward looking economy into a dynamic digitally empowered society. Nearly 95% of the foreign exchange inflows in the service sector are contributed by IT and Buisness Process Outsourcing (BPO) industries. Indian government policy was introduced in 1986 and modified in 1988 in relation with the world market policy, Software Technology Parks of India scheme support to attract Foreign Direct Investment. Recent advancement in the field of information and communication has significantly modified the role of IT in all organizations. Enormous growth in IT industry has changed the outsourcing strategy and buying behavior. Organizations can realize more benefits by investing more funds in IT. India is considered a pioneer in software development and a favourite destination for software and IT enabled services. IT industry has produced a revolutionary variation in the economic scenario and a huge number of personnel are working with higher productivity and association with Multi National Corporations (MNCs).